Ablation of solid pellets induced by supra-thermal ions in the far scrape-off layer of DIII-D plasmas. (25th June 2019) - Bortolon, A.; Kramer, G.J.; Maingi, R.; Mansfield, D.K.; Nagy, A.; Roquemore, A.L.; Lunsford, R.; Bykov, I.; Moyer, R.A.; Parks, P.B.; Van Zeeland, M.A.; Nazikian, R.
Abstract: Injection of solid pellets is a key element in several aspects of the operation of a magnetic confinement plasma reactor for fusion applications, including plasma fueling, control and diagnosis. This letter reports observations demonstrating that pellet ablation can begin outside the plasma boundary, by effect of supra-thermal ions, whose orbits, under appropriate conditions, can extend well into the vacuum region. The phenomenon was recorded during plasma discharges in the DIII-D tokamak, combining pulsed modulation of heating neutral beams, with high-frequency injection of sub-millimeter lithium pellets, and it is ascribed to the large fraction of trapped beam ions associated with counter current neutral beam injection. The effect was quantitatively evaluated by means of Monte-Carlo simulations of supra-thermal ion orbits, finding that the heat-deposition was of the order of 50–100 W mm −2, in the region traversed by the lithium pellets before reaching the plasma boundary, which is consistent with the severe pellet deterioration observed for low velocity pellets.